The Quest for Hellenism: Religion, Nationalism and Collective Identities in Greece (1453-1913) - Livanios, Dimitris (The Historical Review/La Revue Historique, 2007)
The main aim of this essay is to offer a critical survey of the development of Greek collective identities, between 1453 and 1913. That period witnessed dramatic transformations, and the arrival of a modernising and Westernising wave, which crashed onto the Greek shores in the late eighteenth and early nineteenth centuries. The ensuing clash between Western and modern ideas of nationalism on the one hand, and time-honoured local mentalities nurtured by Orthodoxy and the Ottoman millet system, on the other, was intense. This paper attempts to chart some salient aspects of that struggle, to discuss the evolution of concepts and words, such as "Hellene" [Έλληνας], "Hellenism" [Ελληνισμός], "Roman" [Ρωμιός] and "Romiosyne" [Ρωμιοσύνη], and to place them within their changing historical context.